Video Company Profile Lembaga Pelatihan Offshore Technology Institute Dalam Membangun Brand Awareness - Putri Andini Arlianisa Utoyo; Gendhy Dwi Harlyan (Politeknik Negeri Batam, 2026)
Offshore Technology Institute (OTI) faces the challenge of building brand awareness amid competition from the job training industry, because the superior program information for HSE, Quality Control, Engineering, and Production has not been packaged attractively and strategically. The research aims to design motion graphics-based video profile as a digital promotional medium to introduce the identity and service of OTI, reach out to prospective participants and business partners, and improve its professional image. The method used was ADDIE with a descriptive quantitative approach through a five-point Likert scale questionnaire. The ±3 minute video in MP4 format contains the history of institutions, mission-vision, training services, facilities, and testimonials of participants with communicative and structured visuals. The trials of 50 respondents (candidate participants, alumni, prospective clients, staff, and partners) on 15 indicators of brand awareness, information effectiveness, visual-narrative preferences, and influence on audience decisions resulted in a total score of 3,358 out of 3,750 (89.55% on average), including the